Frequencies of D19S433 silent alleles in a Japanese population of 1501 individuals and their effect on likelihood ratios calculated in kinship tests. (February 2022) - Watahiki, Haruhiko; Fujii, Koji; Fukagawa, Takashi; Mita, Yusuke; Kitayama, Tetsushi; Mizuno, Natsuko
Highlights: We determined the exact D19S433 silent allele frequency in 1501 Japanese samples. We evaluated the effect of revealing the D19S433 silent allele on kinship tests. Kinship tests were performed using simulated data. Abstract: Although silent alleles in D19S433 typing using the GlobalFiler PCR Amplification Kit have been reported, the exact frequency of the D19S433 silent alleles in population data of 1501 Japanese individuals, which are widely used for the assessment of Japanese STR typing results, is unclear. In this study, we examined the exact D19S433 silent allele frequency in this population data. We newly observed the G32A variant causing silent alleles at D19S433 in five samples. Combining them with data including 30 samples with the variant reported previously, we determined that the total frequency of the silent alleles (i.e. the frequency of the G32A variant) in the 1501 Japanese samples was 0.0117 (35/3002). Using the D19S433 allele frequency data, we evaluated the effect of presence/absence information for the D19S433 silent allele on kinship tests. Likelihood ratios (LRs) were calculated for both simulated parent–child and full sibling cases, revealing that the LR may change by approximately 10 −2 to 10 3 fold when the presence/absence of the D19S433 silent allele is revealed in a kinship test. Therefore, if a sufficiently large or small LR is obtained, there is little need to determine the presence/absence of the D19S433 silent allele in Japanese kinship tests using GlobalFiler. This study will be beneficial for the assessment of Japanese human identification and kinship test results using GlobalFiler.